Knowledge, Attitude and Practice Regarding Hookah Smoking Among Nursing Students in Chitwan, Nepal: A Cross-Sectional Study - Thapa, Namuna; Ghimire, Babita; Upadhyay, Hari Prasad (Journal of National Heart and Lung Society Nepal, 2022)
Background: Tobacco smoking is a leading preventable cause of mortality and morbidity around the world. The objective of this research was to find the level and factors associated with knowledge, attitude, and practice regarding hookah smoking among nursing students. Methods: A cross-sectional analytical study was conducted among 373 bache-lors of nursing students using a non-probability enumerative sampling technique. Collected data were entered into Statistical Package for the Social Services ver-sion 20. Data were analysed by using descriptive and inferential statistical tools. Results: Out of 373 students, 52.3% of them were found to have inadequate knowledge, 53.4% had a positive attitude about hookah smoking, and 30.6% of students used to smoke a hookah. There was a significant statistical association between levels of attitude regarding hookah smoking with family monthly in-come and family history of hookah smoking. Conclusion: The majority of students have inadequate knowledge and have a positive attitude, while practices of hookah smoking are high.